Strategies for the Digital Dissemination and Promotion of Research in the Spanish University System. Analysis of Public Universities through their Institutional Websites - Siso Calvo, Brenda; Arquero Avilés, Rosario; Marco Cuenca, Gonzalo (Revista General de Información y Documentación, 2018)
The main objective of this research focuses on a comparative analysis of the current state of digital dissemination and promotion of research in the Spanish University System. For achieve the objective this study focuses on examine the dissemination and promotion of research activities made by public universities, and what resources they use to allow access to this information by means of their institutional websites. The paper also identifies what strategies universities plan to develop in the nearest future by studying the trends and lines of action contemplated in their plans and/or strategic documents. A systematic and standardized review and data collection was used as methodological tool, by exploring the websites of the 50 public universities included in the Registro de Universidades, Centros y Títulos (RUCT), with a series of indicators previously defined. The results revealed that there has been considerable progress, although there is still a long way to go before the desired level of implementation in terms of availability of resources specifically aimed at the digital dissemination and visibility of research. Lastly, many initiatives have also been identified to determine the growing interest of the institutions in strengthening their strategies along these lines.